2006
DOI: 10.1021/bi060636o
|View full text |Cite
|
Sign up to set email alerts
|

The Unfolded State of NTL9 Is Compact in the Absence of Denaturant

Abstract: Interest in the unfolded state of proteins has grown with the realization that this state can have considerable structure in the absence of denaturants. Natively unfolded proteins, mutations that unfold proteins under native conditions, and changes in pH that induce unfolding are attractive models for the unfolded state in the absence of denaturant. The unfolded state of the N-terminal domain of ribosomal protein L9 (NTL9) was previously shown to contain significant non-native electrostatic interactions [Cho, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 31 publications
4
35
1
Order By: Relevance
“…This finding is consistent with the results of Raleigh et al, who found the K12M mutation to cause a significant stabilization effect (ΔΔG ∼ 2 kcal/mol) and attributed it to destabilization of the unfolded state. 33,53 Their analysis suggests that the destabilization of the unfolded state is due to the non-formation of a nonnative salt bridge between residues 8 and 12 that is formed (at least transiently) in wild-type NTL9. We find evidence for such interactions in our simulations examining the distance profile between residues 8 and 12.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This finding is consistent with the results of Raleigh et al, who found the K12M mutation to cause a significant stabilization effect (ΔΔG ∼ 2 kcal/mol) and attributed it to destabilization of the unfolded state. 33,53 Their analysis suggests that the destabilization of the unfolded state is due to the non-formation of a nonnative salt bridge between residues 8 and 12 that is formed (at least transiently) in wild-type NTL9. We find evidence for such interactions in our simulations examining the distance profile between residues 8 and 12.…”
Section: Discussionmentioning
confidence: 99%
“…A recent series of studies by Raleigh et al 28,33,50,53,[61][62][63][64] focused on NTL9 as a model protein (Fig. 1a) to investigate the effect of electrostatic interactions on protein stability.…”
Section: Thermodynamic and Kinetic Analysis Of Ntl9 Mutantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interest in the U state has increased following the recognition that the structural basis of protein stability cannot be understood without understanding both the folded and the unfolded states (Tanford 1968). It has also been spurred by the discovery of possible organization in the U state (Gillespie and Shortle 1997;Pappu et al 2000;Shortle and Ackerman 2001;Shi et al 2002;Fitzkee and Rose 2005;Anil et al 2006) and by the recognition of a biological role for intrinsically disordered proteins and protein aggregates (Dunker et al 2001;Chiti and Dobson 2006). As interest in the U state has developed, computational models of unfolded proteins have matured.…”
mentioning
confidence: 99%